Doping Nanoscale Graphene Domains Improves Magnetism in Hexagonal Boron Nitride. Issue 12 (27th January 2019) - Fan, Mengmeng; Wu, Jingjie; Yuan, Jiangtan; Deng, Liangzi; Zhong, Ning; He, Liang; Cui, Jiewu; Wang, Zixing; Behera, Sushant Kumar; Zhang, Chenhao; Lai, Jiawei; Jawdat, BenMaan I.; et al.
Abstract: Carbon doping can induce unique and interesting physical properties in hexagonal boron nitride (h‐BN). Typically, isolated carbon atoms are doped into h‐BN. Herein, however, the insertion of nanometer‐scale graphene quantum dots (GQDs) is demonstrated as whole units into h‐BN sheets to form h‐CBN. The h‐CBN is prepared by using GQDs as seed nucleations for the epitaxial growth of h‐BN along the edges of GQDs without the assistance of metal catalysts. The resulting h‐CBN sheets possess a uniform distrubution of GQDs in plane and a high porosity macroscopically. The h‐CBN tends to form in small triangular sheets which suggests an enhanced crystallinity compared to the h‐BN synthesized under the same conditions without GQDs. An enhanced ferromagnetism in the h‐CBN emerges due to the spin polarization and charge asymmetry resulting from the high density of CN and CB bonds at the boundary between the GQDs and the h‐BN domains. The saturation magnetic moment of h‐CBN reaches 0.033 emu g −1 at 300 K, which is three times that of as‐prepared single carbon‐doped h‐BN. Abstract : The heterostructure of graphene domain/hexagonal boron nitride (h‐BN) is fabricated by epitaxially growing h‐BN at the edge of graphene quantum dots (GQDs, "seed nucleation"). The good crystallinity of the GQDs improves the crystal structue of h‐BN. The CN and CB bonds in the heterostructure enhance the magnetism of h‐BN. Furthermore, the doping of GQDs narrows the bandgap of h‐BN.